A new groundwater species of Pseudoniphargus (Amphipoda: Pseudoniphargidae) fromAlgeria - Dole-Olivier, Marie-Jose; Hafid, Hinda; Piscart, Christophe (Zootaxa, 2018)
Intensive sampling performed in the area of Oum El Bouaghi (Northeastern Algeria) yielded a new species of the stygobiont amphipod Pseudoniphargus, P. djemoi, in wells located in the plain of Tamlouka. The new species belongs to a group that shares the display of a uropod 3 exopod extremely elongate and upcurved in the male, whereas its peduncle is only moderately elongate. This cluster of species appears scattered across the southern Iberian Peninsula, Northern Morocco and the Canary Islands. This discovery increases the number of described species of the stygobiont amphipod genus Pseudoniphargus in north Africa to eight. A key to the species of Pseudoniphargus living in Continental Africa and Mediterranean Islands is provided.